RETRACTED ARTICLE: KiVa anti-bullying program: preventing and reducing bullying behavior among students – a scoping review - Rohman Hikmat; Suryani Suryani; Iyus Yosep; Rohani Jeharsae (BMC Public Health)
Abstract Bullying is a serious problem among adolescents that often occurs in schools. The problem occurs because of the high level of bullying behavior. Bullying causes negative impacts such as anxiety, low self-esteem, and suicide risk. So that interventions are needed to prevent and reduce bullying behavior. The aim of this study is to explore the effectiveness and implementation methods of the KiVa anti-bullying program for preventing and reducing bullying behavior for students. Scoping review design was used in this study using PRISMA Extension for Scoping Review search strategy. A scoping review of studies indexed in CINAHL, PubMed and Scopus databases was conducted. After duplicates were removed and articles screened, 11 studies were included in the review. Data analysis in this study used descriptive qualitative. The 11 included studies comprised of randomized controlled trials and quasi-experimental studies involving range of samples from 1051 to 23.520 respondents from elementary school to high school students aged 6–15 years. The KiVa Anti-bullying intervention was effective for reducing bullying behavior in students (p value < 0.05). This intervention involves teachers, government, students, and health workers to collaborate in building a bullying prevention system. The activities carried out are providing education, assertive and empathy training, role play, counseling, and games. The method in implementing the intervention is online and offline. This therapy can be optimized by providing special interventions to victims, perpetrators, and both. The provision of interventions also needs to be carried out and monitored regularly to prevent repeated bullying behavior in students. The development of online interventions is needed to prevent bullying in students so that it can reach students widely.